Analisis Hambatan Ibu Dalam Pemberian ASI Eksklusif Pada Bayi 0-6 Bulan Di Wilayah Kerja Puskesmas Montasik Kabupaten Aceh Besar - Riadhul Jannah; Fauziah Fauziah; Khaira Rizki (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The primary causes of mortality among infants are diarrhea and pneumonia. But, more than 50% of the cases were caused by malnutrition. Exclusive breastfeeding (6 months to 2 years) and providing complementary nutritious food have proven to be effective interventions in reducing the Infant Mortality Rate (IMR). This study aims to analyze maternal barriers to exclusive breastfeeding for infants aged 0-6 months in Montasik Public Health Center, Aceh Besar. This study used an analytical design with a cross-sectional approach. The population was 147 women. 60 respondents were chosen as the sample using a proportional random sampling technique. It was conducted on May 2nd–18th, 2024. The analysis uses univariate and bivariate Chi-square tests. The results showed that of 60 respondents, most of them provided non-exclusive breastfeeding for 34 respondents (56,7%), early adulthood for 32 respondents (53,3%), middle-class education level for 24 respondents (40%), self-employed for 33 respondents (55%), had sufficient knowledge of breastfeeding as 24 respondents (40%), and did not have a supportive workplace in giving exclusive breastfeeding as 34 respondents (56,7%). In conclusion, there is a correlation between age, education level, work status, knowledge, and environment towards exclusive breastfeeding. It is expected that the community health center will conduct socialization regarding exclusive breastfeeding by holding antenatal classes for a better understanding of exclusive breastfeeding.